Neoliberal Ideology in France: A Qualitative Inquiry - Girerd, Lola; Verniers, Catherine; Bonnot, Virginie (Frontiers in Psychology, 2021)
This article adds to the existing literature on neoliberal ideology by investigating its content and contours in a context historically marked by statism. Very few studies in social psychology have looked at how neoliberal ideology transpires out of people’s discourses and none have done so in such contexts. Yet, this appears necessary in order to better understand its actual influence and how it interacts with localized norms. Relying on a qualitative analysis of 32 semi-structured interviews and on the existing literature, we identified five central themes of neoliberal ideology in France: State prerogatives, competition, abstraction from institutional and social contexts, the entrepreneurial self and emotional management. Results suggest that the influence of neoliberal ideology transpires in the way people envision competition as something natural and motivating, in the way they distance themselves from their immediate and distant contexts, and in the way they value and engage in self-regulation while pursuing happiness and self-optimization. We also found that, in the French context, neoliberal ideology was not necessarily associated to the willingness to see the State step back and to the rationalization of all types of inequalities. Indeed, in the eyes of participants, the State largely remains the guarantor of public services and should ensure an equality of opportunity. This study highlights the value of relying on a qualitative approach to provide a rich and complex account of social realities such as ideologies.